2020
DOI: 10.11606/s1518-8787.2020054001888
|View full text |Cite
|
Sign up to set email alerts
|

Inatividade física no lazer e na escola está associada à presença de transtornos mentais comuns na adolescência

Abstract: OBJETIVO: Investigar a associação da inatividade física no lazer e na escola com os transtornos mentais comuns durante a adolescência. MÉTODOS: A amostra foi composta por 73.399 adolescentes (12–17 anos), participantes do Estudo de Riscos Cardiovasculares em Adolescentes (Erica). Esse estudo transversal, nacional e de base escolar foi realizado em 2013 e 2014, nos municípios brasileiros com mais de 100 mil habitantes. A atividade física no lazer foi categorizada de acordo com o volume de prática semanal, e os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
8
0
11
Order By: Relevance
“…The results of previous studies on the effects of leisure time on mental health remain limited. Most are based on self-assessment questionnaires (see, for example, Badura et al, 2015;Tamminen et al, 2020;Ferreira et al, 2020) or are focus on current mental health issues (e.g. Doré et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies on the effects of leisure time on mental health remain limited. Most are based on self-assessment questionnaires (see, for example, Badura et al, 2015;Tamminen et al, 2020;Ferreira et al, 2020) or are focus on current mental health issues (e.g. Doré et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that there is improvement in the mental health status of children and adolescents with the practice of several types of physical activities 7,8 . Thus, physical activity is an alternative to control and prevent mental health problems in school-aged children and adolescents 9 . The practice of sports, physical education at school and leisure-time physical activity, even without reaching the current recommendation, are related to the good mental health among young people 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, physical activity is an alternative to control and prevent mental health problems in school-aged children and adolescents 9 . The practice of sports, physical education at school and leisure-time physical activity, even without reaching the current recommendation, are related to the good mental health among young people 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, sabe-se que um maior nível de atividade física está associada a uma melhora nos padrões comportamentais (4)(5)(6) , assim, as aulas de educação física tornam-se um ponto fundamental e indispensável para que os alunos se desenvolvam e tenham uma melhora em suas variáveis físicas, psicológicas e sociais (7) . Em um estudo realizado por Ferreira et al (8) verificou-se que existe uma relação positiva entre a prática de exercícios físicos e lazer e o bom desempenho acadêmico em estudantes do ensino fundamental e médio. Os resultados do estudo sugerem que a prática esportiva, as aulas de educação física escolar e a atividade física durante o lazer possuem uma relação intrínseca com a saúde mental dos jovens (8) .…”
Section: Introductionunclassified
“…Em um estudo realizado por Ferreira et al (8) verificou-se que existe uma relação positiva entre a prática de exercícios físicos e lazer e o bom desempenho acadêmico em estudantes do ensino fundamental e médio. Os resultados do estudo sugerem que a prática esportiva, as aulas de educação física escolar e a atividade física durante o lazer possuem uma relação intrínseca com a saúde mental dos jovens (8) .…”
Section: Introductionunclassified